Ultrasonografia trójwymiarowa – doniesienie wstępne - Kosmala, Jacek (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Three-dimensional ultrasound tomography of the eye is a new advanced technique of ocular ultrasonography. The aim of this work was to present a new interesting ultrasound unit with possibility of three-dimensional ultrasound tomography, after half year experience with this system. The article describes scanning techniques using a commercial 3-D ultrasound system (OTIScan 1000) and presents how to assess the dimensions of intraocular structures and document them volumetrically.